Adequate dietary protein level enhances stress resistance and immune status of blunt snout bream (Megalobrama amblycephala Yih, 1955). (24th October 2016) - Habte‐Tsion, H.‐M.; Ren, M.‐C.; Ge, X.‐P.; Kumar, V.; Liu, B.; Xie, J.; Chen, R.‐L.
Summary: This study hypothesized that an optimum dietary protein level might play an important role in improving stress tolerance, enhancing an immune function, and ultimately minimizing temperature stress. For this purpose, the present study conducted a 10‐week feeding trial followed by a 7‐day stress experiment to evaluate the effects of dietary protein levels (28%–36%) on the physiological performances and hepatic Hsp70 gene expression in blunt snout bream Megalobrama amblycephala fry under a high temperature challenge. Fish fry (initial weight, 16.08 ± 0.03 g, n = 25) were fed with their respective diets to apparent satiation, and samples taken once before stress and four times during high temperature stress days (0.125, 0.5, 2 and 7 days). Serum total protein and cholesterol contents before stress were affected by dietary protein levels; during stress these parameters showed no significant changes up until day 2, showing some changes thereafter. Regardless of 0.125, 0.5, 2 or 7 days during stress, cortisol and aspartate aminotransferase levels in the group fed 32% dietary protein were significantly lower than in the other groups. At 0.125, 0.5 or 2 days during stress, the complement component 3 (C3) and 4 (C4) levels increased significantly up to certain levels, declining thereafter. The expression level of Hsp70 mRNA before stress was not affected by dietary protein levels, but increased significantly from 0.125 to 0.5 days during stress, and was reduced thereafter. Overall, low cortisol and high C3, C4 and Hsp70 mRNA levels were found in the group fed 32% protein throughout the stress experiment, which indicated that an adequate protein level enhances stress resistance and immunity in fish.